RAPID AND ECONOMICAL QUANTITATIVE DETERMINATION OF SEVERAL ANTIHYPERTENSIVE AGENTS IN PRESENCE OF HYDROCHLOROTHIAZIDE BY ISOCRATIC REVERSED-PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY IN THEIR PHARMACEUTICAL PREPARATIONS - Ravisankar, Panchumarthy; G, Devala Rao; Sulthana, Md. Shaheem; K, Supriya; G, Mounika; P, Naveena (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Objective of the present investigation is to develop a speedy isocratic reverse phase high-performance liquid chromatography (RP-HPLC) method for the separation and quantitative determination of 5 angiotensin II - receptor antagonists, namely, telmisartan, losartan, valsartan, olmesartan, irbesartan, and atenolol along with thiazide diuretics mostly hydrochlorothiazide (HCTZ). Methods: RP-HPLC method was evolved using Welchrom C18 column (4.6 Ã— 250 mm, 5 Î¼m) as a stationary phase with the mobile phase comprising a variety of phosphate buffer with pH-3.3 and acetonitrile in the proportion of 50:50 v/v. The mobile phase was pumped at a current rate of 1 mL/minute. The detection wavelength was carried out at 230 nm. Results: The total run time was 6 minutes and the elution window of only 3 minutes. The peaks were eluted with decorous resolution. The calibration curves were linear (r2=0.9998) in all cases. The percentage relative standard deviation (RSD%) was <2% and average recovery was above 99.95%. The method was validated specificity, precision, and accuracy. High recovery values and low RSD% prove that this method is very accurate and reproducible. The developed method was applied to the estimation of the above-said drugs in binary combinations from different manufacturers which were a good agreement with label claim. Conclusion: The important advantage of developed method was that the five individual drugs can be determined on a single chromatographic system without alteration in detection wavelength and mobile phase composition. This novel method was statistically validated as per ICH guidelines. The optimized method proved to be linear, accurate, and robust. Hence, the above said proposed method was found to be a rapid tool for the routine determination of the above-said drugs in alone or combination with HCTZ in quality control analysis without interference of excipients.